2008
DOI: 10.1299/jfst.3.466
|View full text |Cite
|
Sign up to set email alerts
|

Performance Prediction of OWC Type Small Size Wave Power Device with Impulse Turbine

Abstract: This paper investigates a small size wave power device with an impulse turbine installed in the breakwater near Niigata Port, Japan. The device consists of an air chamber, a turbine, a generator and pressure-relief valves. This study reveals the characteristics of each component in this system with impulse turbine and a direct current dynamo the power of which is consumed by a constant resistor. In this paper special features of the impulse turbine are found, and the system characteristics are briefly represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Unidirectional axial impulse turbine has been employed in both fixed and floating type OWC based wave energy plants [43][44][45][46]. Numerical simulations on twin unidirectional turbines have been found to be most suitable for the Indian fixed wave power plant as reported by Jayashankaret al [43] and for the floating wave power device, backward bent duct buoy (BBDB) as reported by Dudhgaonkaret al [46] as part of wave energy program conducted by National Institute of Ocean Technology, Chennai.…”
Section: A Unidirectional Turbinementioning
confidence: 99%
See 1 more Smart Citation
“…Unidirectional axial impulse turbine has been employed in both fixed and floating type OWC based wave energy plants [43][44][45][46]. Numerical simulations on twin unidirectional turbines have been found to be most suitable for the Indian fixed wave power plant as reported by Jayashankaret al [43] and for the floating wave power device, backward bent duct buoy (BBDB) as reported by Dudhgaonkaret al [46] as part of wave energy program conducted by National Institute of Ocean Technology, Chennai.…”
Section: A Unidirectional Turbinementioning
confidence: 99%
“…The performance comparison of axial impulse turbine types has been reported by several articles [43][44][45][46][64][65][66][67]. Takao et al [64] observed that the efficiency of the axial impulse turbine with self-pitch-controlled guide vanes is higher over a wider range of flow coefficients in comparison with the axial impulse turbine with fixed vanes under irregular flow conditions.…”
Section: Viicomparision Of Impulse Turbinesmentioning
confidence: 99%
“…A sea trial of wave power plant using an impulse turbine with coreless generator has been carried out at Niigata-Nishi Port, in order to demonstrate usefulness of the turbine for wave energy conversion [40,41]. As shown in Figure 15, OWC-based wave power plant has been installed at the side of a breakwater and has an air chamber with a sectional area of 4 m 2 (= 2 m × 2 m).…”
Section: Sea Trial Of Air Turbinesmentioning
confidence: 99%
“…121 To predict the performance of the turbines, analytical calculations expressed in torque, input power, and flow coefficients can be useful for initial estimations. 113,122 Furthermore, Thakker and Dnanasekaran have shown a good correspondence between a CFD model and experimental results in their study to show the large influence of the tip clearance on the turbine efficiency. 116 However, one should be careful with using these methods blindly for thermoacoustics because they assume a quasi-steady flow.…”
Section: Characteristicsmentioning
confidence: 84%
“…For the conversion of acoustic power into electricity, an axial impulse turbine is used which is based on the work from Suzuki et al for an OWC. 122 A schematic of this turbine mounted in a tube section is shown in Fig. 3.2.…”
Section: Turbine Designmentioning
confidence: 99%